Tra Dio e la macchina. Il problema della trascendenza te(cn)ologica del primo Blumenberg - Battista, Ludovico (Mechane, 2021)
This article aims to briefly analyses some considerations on technology by a young Hans Blumenberg, in order to show how his first philosophical inquiry had identified a close link between theological and technological questions. Starting from a Heideggerian reflection on the “demonic nature” of technology, the philosopher had in fact recognized in the “destructive” and potentially nihilistic experience of transcendence the common denominator between the idea of God and the modern machine. The reconstruction of this abruptly interrupted path of blumenbergian reflection casts a considerable light on its subsequent development, and in particular on its insistence on the figure of Faust and the problem of the Goethian demonism.